Reduced Albumin Concentration Predicts Weight Gain and Higher Ad Libitum Energy Intake in Humans - Basolo, Alessio; Ando, Takafumi; Chang, Douglas C.; Hollstein, Tim; Krakoff, Jonathan; Piaggi, Paolo; Votruba, Susanne (Frontiers in Endocrinology, 2021)
Circulating albumin is negatively associated with adiposity but whether it is associated with increased energy intake, lower energy expenditure or weight gain has not been examined. In study 1 (n=238;146 men), we evaluated whether fasting albumin concentration was associated with 24-hour energy expenditure and ad libitum energy intake. In study 2 (n=325;167 men), we evaluated the association between plasma albumin and change in weight and body composition. After adjustment for known determinants of energy intake lower plasma albumin concentration was associated with greater total daily energy intake (β= 89.8 kcal/day per 0.1 g/dL difference in plasma albumin, p=0.0047). No associations were observed between plasma albumin concentrations and 24h energy expenditure or 24h respiratory quotient (p>0.2). Over 6 years, volunteers gained on average 7.5±11.7 kg (p<0.0001). Lower albumin concentrations were associated with greater weight (β=3.53 kg, p=0.039 [adjusted for age, sex, follow up time], CI 0.16 to 6.21 per 1 g/dL difference albumin concentration) and fat mass (β=2.3 kg, p=0.022), respectively, but not with changes in fat free mass (p=0.06). Lower albumin concentrations were associated with increased ad libitum food intake and weight gain, indicating albumin as a marker of energy intake regulation.